A Brief Overview of a Round Table Discussion About Venous Thromboembolism in Pregnancy During the First International Forum on Chinese Maternal-Fetal Medicine. Issue 3 (23rd July 2020) - Wang, Chen; Yang, Hui-Xia
Abstract : Abstract: Venous thromboembolism (VTE) is a leading cause of maternal morbidity and mortality though with low rates. Compared to non-pregnant women of comparable age, women during pregnancy have five- to ten-fold increased risk of VTE, additional risk factors for VTE during pregnancy include a personal history of thrombosis, the presence of a thrombophilia, cesarean delivery, obesity, hypertension, preeclampsia, autoimmune disease, heart disease, sickle cell disease and multiple gestation. Thus, early clinical evaluation, preferably in peri-conceptional period, is crucial for VTE risk detection and, thus, for prophylaxis decision making. VTE thromboprophylaxis brought significant advantages in pregnancy outcomes and maternal deaths. Common pharmacological and mechanical forms of thromboprophylaxis includes heparin compounds, anti-embolic stockings and intermittent pneumatic compression devices. Low-molecular-weight heparin as first line strategy. Current guidelines or expert opinions on VTE treatment or prophylaxis during pregnancy diverge significantly. High quality research in this area is still needed, and China needs to develop its own VTE guidelines. Importantly, absolute risks and potential benefits of VTE thromboprophylaxis should be evaluated to make the best decisions on VTE screening, prevention, and treatment.